Pigment Epithelium-derived Factor (PEDF) mitigates inflammation and oxidative stress in retinal pericytes exposed to oxidized-LDL - Zhang, Sarah X. (2008)
Oxidized and/or glycated LDL may mediate capillary injury in diabetic retinopathy. The mechanisms may involve pro-inflammatory and pro-oxidant effects on retinal capillary pericytes. In this study, these effects, and the protective effects of pigment epithelium-derived factor (PEDF), were defined in a primary human pericyte model. Human retinal pericytes were exposed to 100 µg/ml of native LDL (N-LDL) or heavily oxidized glycated LDL (HOG-LDL) with or without PEDF at 10–160 nM for 24 h. To assess pro-inflammatory effects, monocyte chemoattractant protein-1 (MCP-1) secretion was measured by ELISA, and nuclear factor kappa B (NF-κB) activation was detected by immunocytochemistry. Oxidative stress was determined by measuring intracellular reactive oxygen species (ROS), peroxynitrite (ONOO(−)) formation, inducible nitric oxide synthase (iNOS) expression and nitric oxide (NO) production. The results showed that MCP-1 was significantly increased by HOG-LDL, and the effect was attenuated by PEDF in a dose-dependent manner. PEDF also attenuated the HOG-LDL-induced NF-κB activation, suggesting that the inhibitory effect of PEDF on MCP-1 was at least partially through the blockade of NF-κB activation. Further studies demonstrated that HOG-LDL, but not N-LDL, significantly increased ONOO(−) formation, NO production, and iNOS expression. These changes were also alleviated by PEDF. Moreover, PEDF significantly ameliorated HOG-LDL-induced ROS generation through up-regulation of SOD1 expression. Taken together, these results demonstrate pro-inflammatory and pro-oxidant effects of HOG-LDL on retinal pericytes, which were effectively ameliorated by PEDF. Suppressing MCP-1 production and thus inhibiting macrophage recruitment may represent a new mechanism for the salutary effect of PEDF in diabetic retinopathy and warrants more studies in future.